Continental-scale temperature variability during the past two millennia - Ahmed, Moinuddin; Anchukaitis, Kevin J.; Asrat, Asfawossen; Borgaonkar, Hemant P.; Braida, Martina; Buckley, Brendan M.; Büntgen, Ulf; Chase, Brian M.; Christie, Duncan A.; Cook, Edward R.; Curran, Mark A. J.; Diaz, Henry F.; et al. (Nature Geoscience, 2013)
Past global climate changes had strong regional expression. To elucidate their spatio-temporal pattern, we reconstructed past temperatures for seven continental-scale regions during the past one to two millennia. The most coherent feature in nearly all of the regional temperature reconstructions is a long-term cooling trend, which ended late in the nineteenth century. At multi-decadal to centennial scales, temperature variability shows distinctly different regional patterns, with more similarity within each hemisphere than between them. There were no globally synchronous multi-decadal warm or cold intervals that define a worldwide Medieval Warm Period or Little Ice Age, but all reconstructions show generally cold conditions between ad 1580 and 1880, punctuated in some regions by warm decades during the eighteenth century. The transition to these colder conditions occurred earlier in the Arctic, Europe and Asia than in North America or the Southern Hemisphere regions. Recent warming reversed the long-term cooling; during the period ad 1971–2000, the area-weighted average reconstructed temperature was higher than any other time in nearly 1,400 years.